Rapid weight loss in competitive judo and taekwondo athletes: Attitudes and practices of coaches and trainers - Berkovich, B.-E.; Stark, A. H.; Eliakim, A.; Nemet, D.; Sinai, T. (International Journal of Sport Nutrition and Exercise Metabolism, 2019)
Fasting, skipping meals, and dehydration are common methods of rapid weight loss used prior to competition in weight category sports. This study examines coaches` attitudes, perceptions, and practices regarding rapid weight loss among judo and taekwondo athletes. A convenience sample of experienced coaches and trainers (n = 68) completed structured questionnaires. Participants in this study were 33.8 ± 9.3 years old; 57 were males and 11 were females; and 59% were certified coaches, with 71% reporting over 20 years of involvement in sports and 68% having more than 10 years of teaching experience. The majority (90%) reported that they usually supervised athletes through the weight loss process. Interventions for weight loss began at 12.7 ± 1.9 years of age, with a recommended precompetition weight loss duration of 16.2 ± 8.2 days and an average reduction of 1.5 ± 0.7 kg. The majority of the responders (92%) recommended that their athletes practice gradual weight loss methods using a combination of dehydration or increased physical activity (80.3%), sweat suits (50.8%), restricted fluid intake (39.3%), training in heated rooms (27%), and sauna (26.2%). Recommendations of spitting (27.8%) or using laxatives, diuretics, diet pills, or vomiting (21.3%) were also reported. Coaches and trainers often encouraged athletes to cut weight before competition. The methods recommended are potentially harmful with severe health risks, including compromised nutritional status and diminished athletic performance. This is of particular concern in young athletes who are still growing and developing physically. Enhancing knowledge and awareness for coaches, athletes, and parents regarding potential dangers, along with improved nutrition education, is critical for reducing the magnitude and misuse of rapid weight loss methods.